Effect of micro climatic indices on the accuracy of thermographic plant water status monitoring, case study of a semi-arid area. Issue 5 (20th October 2021) - Shoa, Pedram; Hemmat, Abbas; Gheysari, Mahdi; Amirfattahi, Rassoul
ABSTRACT: Plant water stress can be remotely monitored by means of thermography due to its increasing effect on plant temperature. For a more accurate estimation of plant water status, its temperature should be normalised against environmental conditions. In this paper, the aim was to investigate a recently proposed method of normalisation using artificial reference surfaces, different measurement times in a day and different capturing directions regarding to solar trail. At three different times of the day, frontal images were captured from the sunlit side of the olive canopies in two azimuth directions. Two different stress indices of crop water stress index (CWSI) and stomatal conductance index (IG ) were calculated using Tc and the temperatures of wet and dry reference surfaces. Trees in different stress levels discriminated better via mean canopy temperature (Tc) of morning measurements. At this time, Tc also provided higher correlated indices with stomatal conductance (SC) rather than those indices calculated based on Tc measured at noon and afternoon. Comparing two measurement directions, the first direction provided Tc with higher correlated indices at morning but the second direction at afternoon. In the most of the measurement conditions, stress indices calculated with air temperature plus five degrees as dry reference temperature had higher correlation with SC.